La relación entre el control interno y la gestión administrativa de la Municipalidad de Trompeteros durante el periodo 2022 - Diaz Panduro, Roy Gabriel (2024)
This study investigated the relationship between internal control and administrative management in the Municipality of Trompeteros during the year 2022. Through a non-experimental quantitative approach of analytical design, data from 142 employees were collected and examined using Spearman's correlation coefficient. The results indicated a significant positive correlation between internal control and the effectiveness of administrative management (Spearman's rho = 0.7721, p-value = 0.047), highlighting the importance of supervision, risk assessment and regulatory compliance processes. Likewise, a moderate positive relationship was identified between risk assessment and operational efficiency (Spearman's rho = 0.6382, p-value = 0.039), as well as between communication and internal reporting and service quality (Spearman's rho = 0.5428, p-value = 0.0261). These results suggest that the effective implementation of internal control practices is essential to improve resource management, project execution and service delivery in the municipality. The study provides empirical support for the implementation of strategies aimed at strengthening internal control for more effective and transparent administrative management at the municipal level.